2007
DOI: 10.1021/la062299q
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilicity and the Viscosity of Interfacial Water

Abstract: We measure the viscosity of nanometer-thick water films at the interface with an amorphous silica surface. We obtain viscosity values from three different measurements: friction force in a water meniscus formed between an oxide-terminated W tip and the silica surface under ambient conditions; similar measurements for these interfaces under water; and the repulsive "drainage" force as the two surfaces approach at various speeds in water. In all three cases, we obtain effective viscosities that are approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
206
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(227 citation statements)
references
References 41 publications
19
206
1
Order By: Relevance
“…As an approach to study attractive regimes, friction forces have been measured using the IFM (Joyce & Houston, 1991), where the force feedback makes it possible. (Burns et al, 1999a;Goertz et al, 2007;Major et al, 2006). Burns et al applied IFM to measure friction force and normal force simultaneously to study the molecular nature of friction to investigate the intermolecular friction along with normal forces in the attractive regime (Burns et al, 1999a).…”
Section: Molecular Interactions 126mentioning
confidence: 99%
See 3 more Smart Citations
“…As an approach to study attractive regimes, friction forces have been measured using the IFM (Joyce & Houston, 1991), where the force feedback makes it possible. (Burns et al, 1999a;Goertz et al, 2007;Major et al, 2006). Burns et al applied IFM to measure friction force and normal force simultaneously to study the molecular nature of friction to investigate the intermolecular friction along with normal forces in the attractive regime (Burns et al, 1999a).…”
Section: Molecular Interactions 126mentioning
confidence: 99%
“…The tip-speed was controlled by the built-in digital-to-analog converter of the RHK controller in conjunction with the high-voltage amplifier. The lateral movement was achieved by dithering the sample in the long axis direction of the cantilever, using the piezo tube with an oscillatory signal of about 1 nm amplitude at the frequency of 100 Hz (Goddenhenrich et al, 1994;Goertz et al, 2007;Major et al, 2006). A Hewlett-Packard function generator (model 33120A) was used to generate the oscillatory signal.…”
Section: Molecular Interactions 128mentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrophilic conversion and reduction in polarity contrast due to the osmiophilic interlayer further encourages the encapsulation of the fibers by a viscous interfacial water layer (left). [3][4][5] water, we are justified in assuming that most of the mobile molecules surrounding the elastic fibers are water molecules. This picture leaves room for an energy minimizing argument, related to the possible organization of the interfacial water on elastic fibers performing their function: From previous work we concluded that crystalline water layers immobilized on hydrophobic substrates are instrumental in reducing dissipative effects at the solid-liquid interface during evaporative processes.…”
mentioning
confidence: 99%